2017
DOI: 10.3389/fmed.2017.00188
|View full text |Cite
|
Sign up to set email alerts
|

Is Delirium the Cognitive Harbinger of Frailty in Older Adults? A Review about the Existing Evidence

Abstract: Frailty is a clinical syndrome defined by the age-related depletion of the individual’s homeostatic reserves, determining an increased susceptibility to stressors and disproportionate exposure to negative health changes. The physiological systems that are involved in the determination of frailty are mutually interrelated, so that when decline starts in a given system, implications may also regard the other systems. Indeed, it has been shown that the number of abnormal systems is more predictive of frailty than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 107 publications
1
33
0
2
Order By: Relevance
“…It has also been shown how delirium might indeed be a significant predictor of the occurrence of ACE along with older age, malnutrition, acute infection and indwelling bladder catheter in older patients admitted to rehabilitation settings with cardiological, neurological, pulmonary and orthopedic diagnoses . The latter study further suggests the importance of delirium as an epiphenomenon of underlying frailty that might indeed predispose patients to adverse clinical outcomes or might be the expression of an inadequate recognition of the presence of delirium leading to a delayed treatment of the underlying causes . More recently, Gleason et al reported how the coexistence of post‐surgical delirium and complications in a population of older patients who underwent elective surgery was significantly associated with adverse outcomes, including prolonged length of stay, readmission and institutional discharge .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has also been shown how delirium might indeed be a significant predictor of the occurrence of ACE along with older age, malnutrition, acute infection and indwelling bladder catheter in older patients admitted to rehabilitation settings with cardiological, neurological, pulmonary and orthopedic diagnoses . The latter study further suggests the importance of delirium as an epiphenomenon of underlying frailty that might indeed predispose patients to adverse clinical outcomes or might be the expression of an inadequate recognition of the presence of delirium leading to a delayed treatment of the underlying causes . More recently, Gleason et al reported how the coexistence of post‐surgical delirium and complications in a population of older patients who underwent elective surgery was significantly associated with adverse outcomes, including prolonged length of stay, readmission and institutional discharge .…”
Section: Discussionmentioning
confidence: 91%
“…29 The latter study further suggests the importance of delirium as an epiphenomenon of underlying frailty that might indeed predispose patients to adverse clinical outcomes or might be the expression of an inadequate recognition of the presence of delirium leading to a delayed treatment of the underlying causes. 16 More recently, Gleason et al reported how the coexistence of post-surgical delirium and complications in a population of older patients who underwent elective surgery was significantly associated with adverse outcomes, including prolonged length of stay, readmission and institutional discharge. 19 The present study provides further insights on the possible relationship between delirium and clinical status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium is defined by the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders as a transient neurocognitive disorder, characterized by an acute onset and fluctuating course, inattention, cognitive dysfunction, and behavioral abnormalities, which develops in association with another underlying medical condition. It is possible that delirium causes motor fluctuations, such as myoclonus or tremulousness, due to the disruptors of key central neurotransmitters (for example, related to attentive and executive functions) leading to an inability in planning and sustaining movement pathways [42]. While current literature does not clearly define its cause, delirium has a consistent presentation that reflects dysfunction of a final common neural pathway [43][44][45] -or "all" pathways.…”
Section: Methods/theorymentioning
confidence: 99%
“…They found that the prefrontal cortices, anterior and right thalamus, and right basilar mesial temporoparietal cortex may play a significant role in subserving delirium symptoms and maybe the 'final common pathway' for delirium from a variety of etiologies. Bellelli et al [42] contribute that the physiological systems which are involved in the determination of frailty, including the brain, endocrine system, immune system, and skeletal muscle are mutually interrelated. Therefore, we conclude that the degeneration of the neural circuit responsible for the onset of delirium, may initiate a cascade of disruption of the temporal disruption of the mechanisms that drive the stimulation and communication of such areas in the brain, ultimately decreasing the strength and vitality of crucial synapses, leading to a multidimensional loss of body functions, a type of accelerated aging.…”
Section: Methods/theorymentioning
confidence: 99%